Malaria trends in Ethiopian highlands track the 2000 ‘slowdown’ in global warming - Xavier Rodó (Nature Portfolio, 2021)
The effect of climate change on highland malaria transmission remains unclear because of increasing and decreasing trends. Here, Rodó et al. analyze malaria case data and climate data for the Ethiopian highlands from 1968 to 2008 and find that changes in temperature and associated climate variability facilitated the effect of interventions at the beginning of the 21st century.